PPAR-γ Regulates Trophoblast Differentiation in the BeWo Cell Model - Khrystyna Levytska; Sascha Drewlo; Dora Baczyk; John Kingdom (PPAR Research)
Common pregnancy complications, such as severe preeclampsia and intrauterine growth restriction, disrupt pregnancy progression and impair maternal and fetal wellbeing. Placentas from such pregnancies exhibit lesions principally within the syncytiotrophoblast (SCT), a layer in direct contact with maternal blood. In humans and mice, glial cell missing-1 (GCM-1) promotes differentiation of underlying cytotrophoblast cells into the outer SCT layer. GCM-1 may be regulated by the transcription factor peroxisome proliferator-activated receptor-gamma (PPAR-γ); in mice, PPAR-γ promotes labyrinthine trophoblast differentiation via Gcm-1, and, as we previously demonstrated, PPAR-γ activation ameliorates disease features in rat model of preeclampsia. Here, we aimed to characterize the baseline activity of PPAR-γ in the human choriocarcinoma BeWo cell line that mimics SCT formation in vitro and modulate PPAR-γ activity to study its effects on cell proliferation versus differentiation. We report a novel negative autoregulatory mechanism between PPAR-γ activity and expression and show that blocking PPAR-γ activity induces cell proliferation at the expense of differentiation, while these remain unaltered following treatment with the agonist rosiglitazone. Gaining a deeper understanding of the role and activity of PPAR-γ in placental physiology will offer new avenues for the development of secondary prevention and/or treatment options for placentally-mediated pregnancy complications.